COMMUNICATION PATTERNS OF THE MANGUNAN DISTRICT GOVERNMENT TO THE COMMUNITY IN MANAGING VILLAGE TOURISM POTENTIALS - Salim, Mufid; Pangestu, Sony; Barykin, Sergey; Longani, Kirti Dang; Farihanto, M. Najih (ASPIKOM Jabodetabek Region, 2022)
As one of the Special Region of Yogyakarta districts, Mangunan has many tourism potentials, from artistic and cultural attractions, natural beauty, and human resources. It is a pity if the community does not appropriately use it. The district government must take advantage of its potential as a community representative and be trusted as a policymaker. This study aims to determine how the communication patterns carried out by the district government to the community in managing village tourism potential. This research method uses a descriptive qualitative research approach. This study uses data collection methods with structured interviews by conducting interviews with the district government as policymakers and three tourism object managers. For the data analysis technique, the Grounded approach offered by Miles and Huberman and the theory of message dissemination patterns by Guetzkow were used. The results of this study indicate that the communication pattern carried out by the Mangunan District government uses a simultaneous message distribution pattern, utilizing the district government to convey messages or information directly to tourism actors through regular face-to-face meetings and the WhatsApp chat application.